The polymorphism in g.1256G>A of bovine pituitary specific transcription factor-1 (bPIT-1) gene and its association with body weight of Pasundan cattle - Putra, W. P. B.; Agung, P. P.; Said, S. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
Bovine Pituitary specific transcription factor 1 (bPit-1) is one of amino acid that controling pituitary gland in mammals. The pituitary gland is important for secretion of growth hormone from growth genes. This study was carried out to detect polymorphism in the exon 6 of bPit-1 (g.1256G>A) in Pasundan cattle using PCR-RFLP method and its association with body weight. Total of 69 heads (15 males and 54 females) of Pasundan cattle from breeding station (BPPIBT-SP Ciamis, West Java) were used in this study. Research showed that two genotypes of bPit-1/HinfI gene were identified in this study i.e GG (0.90) and AG (0.10) with allele frequencies of 0.05 (A) and 0.95 (G). The polymorphic informative content (PIC) and number of effective allele (ne) values were 0.09 (low) and 1.11. respectively. The Chi-square (χ2) value in the population studied was 0.20 and in Hardy-Weinberg equilibrium (χ2<5.99). It was concluded that the polymorphism of bPit-1/HinfI in Pasundan cattle included of low category and was not associated with body weight.